SACUBITRIL/VALSARTAN IMPROVES SEXUAL FUNCTION AND FIBROSIS OF THE CLITORAL AND VAGINAL TISSUES IN FEMALE SPONTANEOUSLY HYPERTENSIVE RATS. (June 2022) - Zhuang, Chenchen; Wang, Wenjuan; Sun, Runmin; Qi, Miaomiao; Yu, Jing
Abstract : Objective: Female sexual dysfunction is common in hypertension. The effects of sacubitril/valsartan (SAC/VAL) as a potential therapy for hypertension and heart failure have not been studied in relation to sexual function and genital fibrosis in female spontaneously hypertensive rats (SHRs). To evaluate the effect of SAC/VAL on sexual function and genital fibrosis in female SHRs. Design and method: Thirty female SHRs were administered VAL (30 mg/kg/day), SAC/VAL (60 mg/kg/day) or saline. Ten normotensive female Wistar-Kyoto (WKY) rats were included in the control group. We assessed estrous cyclicity and sexual behavior in the female rats. In addition, the morphology of clitoral and vaginal tissues was evaluated by histological analyses. Western blotting and enzyme-linked immunosorbent assays were used to assess the levels of fibrotic markers in vaginal and clitoral tissues. Furthermore, the protein levels of phosphatase and tensin homolog deleted from chromosome 10 (PTEN), phosphoinositide-3-kinase (PI3K) and AKT expression were measured by western blotting. We investigated the effect of SAC/VAL on the fibrosis of vaginal and clitoral tissues, estrus cyclicity and sexual behavior, including sexual receptivity (lordosis quotient and intensity), plus the number of proceptive and aggressive events. Results: SAC/VAL treatment improved hypertension-induced sexual dysfunction, exhibited as a prolonged estrus phase, increased receptivity and proceptive events, and decreased aggressive events, compared to those of VAL treatment and control SHRs without treatments. In addition, SAC/VAL-treated SHRs had lower levels of fibrotic markers than the levels of VAL-treated SHRs or SHRs without treatment. Moreover, SAC/VAL decreased p-PTEN expression and increased p-PI3K and p-AKT expression at the protein level compared to those in VAL treatment alone. Conclusions: SAC/VAL treatment is superior to VAL treatment in attenuating sexual dysfunction and fibrosis of vaginal and clitoral tissues, which may be related to the PTEN/PI3K/AKT pathway.